Chemistry of Biotites and Whole Rocks from the Rapakivi Itu Complex (Late Precambrian), State of São Paulo, SE Brazil - Galembeck, Tamar Milca Bortolozzo [UNESP]; Wernick, Eberhard [UNESP]; Hörmann, Paul Karl (My University, 1997)
Chemical analyses for biotites and their host rocks from the Cabreúva (three facies) and Salto (five facies) intrusions from the multiple-centered rapakivi Itu Complex, State of São Paulo, Brazil, are presented and compared. The Cabreúva intrusion comprises different kinds of mainly even-grained biotite and hornblende-bearing syenogranites, monzogranites and quartz syenites and the Salto intrusion several types of mainly porphyritic biotite syenogranites, some of them hornblende-bearing. The biotites from the Salto intrusion (S-micas) show a more restricted composition than those from the Cabreúva intrusion (C-micas). This reflects the chemical variability of the two bodies which is smaller in the Salto intrusion and larger in the Cabreúva pluton. In the AlIV x Fet/(Fet+Mg) diagram the S- and C-micas show similar AlIV contents, around 2.2-2.3, but C-micas have higher Fet/(Fet+Mg) ratios (0.7-0.9) compared to those of S-micas (0.5-0.6). In the Mg:(Al+Fe+3+Ti):(Fe+2+Mn) diagram the S-micas are defined as Fe+2-biotites and the C-micas occupy the area between the Fe+2-biotites and the siderophyllite/lepidomelane fields, slightly overlapping the latter. In the Al2O3 × FeOt, MgO × FeOt, Al2O3 x MgO and Alt x Mg diagrams, the S-micas always lie on the calc-alkaline/alkaline boundary (or in the subalkaline field) whereas the C-micas systematically plot in the alkaline field, reflecting the higher alkalis content of the Cabreúva intrusion. In the Fet/(Fet+Mg) x SiO2 diagram, the S-micas lie on a smooth line whereas the C-micas from the different facies are separated by distinct chemical gaps reflecting the major or minor chemical overlapping of the facies from the Salto and Cabreúva intrusions.
Keywords: Biotites; Geochemistry; Itu complex; Rapakivi granites; Whole rock